2020
DOI: 10.1609/aaai.v34i04.5967
|View full text |Cite
|
Sign up to set email alerts
|

Learning Weighted Model Integration Distributions

Abstract: Weighted model integration (WMI) is a framework for probabilistic inference over distributions with discrete and continuous variables and structured supports. Despite the growing popularity of WMI, existing density estimators ignore the problem of learning a structured support, and thus fail to handle unfeasible configurations and piecewise-linear relations between continuous variables. We propose lariat, a novel method to tackle this challenging problem. In a first step, our approach induces an SMT(ℒℛA) formu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…This opens up a number of interesting research directions. First, SPLs can be extended to incorporate logical constraints over multiple networks and representable by first-order formulas [45], which we plan to explore in future works, making the circuit construction pipeline totally transparent to users [1] while possibly automatically learning constraints from data [20,47]. Second, we are interested in leveraging SPLs to inject scalable logical constraints into large language models [6] thus equipping them with robust probabilistic reasoning capabilities [29,78].…”
Section: Discussionmentioning
confidence: 99%
“…This opens up a number of interesting research directions. First, SPLs can be extended to incorporate logical constraints over multiple networks and representable by first-order formulas [45], which we plan to explore in future works, making the circuit construction pipeline totally transparent to users [1] while possibly automatically learning constraints from data [20,47]. Second, we are interested in leveraging SPLs to inject scalable logical constraints into large language models [6] thus equipping them with robust probabilistic reasoning capabilities [29,78].…”
Section: Discussionmentioning
confidence: 99%
“…WMC has recently been extended to Weighted Model Integration (WMI), which can be used to solve probabilistic reasoning problems that involve both discrete and continuous probability distributions [114]. It is shown that standard knowledge compilation techniques apply to WMI, leading to exact and approximate solvers [60,113]. Based on this finding, we argue that the proposed partitioning technique in this chapter can extend WMI for representations that are less or equally succinct as d-DNNF when dealing with non-linear real arithmetics.…”
Section: Related Workmentioning
confidence: 99%